2012
DOI: 10.1186/1476-0711-11-28
|View full text |Cite
|
Sign up to set email alerts
|

Aetiological agents of cerebrospinal meningitis: a retrospective study from a teaching hospital in Ghana

Abstract: AbstractsBackgroundMeningitis is an important cause of morbidity and mortality in low-resource settings. In sub-Saharan Africa, the meningitis belt has been characterized by particularly high and seasonal incidences of bacterial meningitis extending throughout life. Despite the progress being made in treating the condition, the mortality rates continue to be high, ranging between 2% and 30% globally. In Ghana, the mortality rate of meningitis has been estimated to range from 36% to 50%. However little informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 39 publications
5
34
0
1
Order By: Relevance
“…Salmonella infection as a cause of bacterial meningitis is reported primarily in tropical areas (1,2), but also occasionally in industrialized countries (3)(4)(5). Most cases of Salmonella meningitis involve children less than 1 year of age, primarily less than 3 months old (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella infection as a cause of bacterial meningitis is reported primarily in tropical areas (1,2), but also occasionally in industrialized countries (3)(4)(5). Most cases of Salmonella meningitis involve children less than 1 year of age, primarily less than 3 months old (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…This difference could be explained by their relatively small sample of 70 patients studied; of which 40 had a bacteriological diagnosis due to the inability of the patients to pay for this test. Pneumococcus is reported as the most frequent causal agent of adult meningitis with proportions varying from 45.2% to 77.7% [5]- [7] [9] [12]. However, two african studies have reported the Pneumococcus as the second most frequent aetiologic agent of bacterial meningitis with proportion of 37.1% in a Tunisian study coming after Haemophilus influenzae [13] and 4.8% coming after Meningococcus in Mozambique [14].…”
Section: Discussionmentioning
confidence: 99%
“…The usual CSF findings are white blood cell count of 1000 to 5000/ µL with the percentage of neutrophils usually greater than 80%, protein > 200 mg/dL, and glucose < 40 mg/ dL. However, there have been reports shown in multiple studies where bacterial meningitis has no CSF abnormalities [8,9].…”
Section: Case Reportmentioning
confidence: 99%